Clinical Pharmacists in Correctional Facilities: A Literature Review and Future Directions. (July 2019) - Thomson, Caitlyn; Gunther, Mary; Macek, Peter
The role of pharmacists has undergone a significant transformation. Expanding clinical roles in the community and hospital settings have led to opportunity for correctional facility pharmacists to expand their practice. This literature review identifies past and present roles of correctional pharmacists, along with areas for growth. Peer-reviewed and gray literature is described, outlining current and expanding pharmacist roles from 1997 to 2017. The literature reveals that health care provided in correctional facilities is shifting from a basic level of care to a greater role in inmate health and identifies the challenges and barriers that pharmacists meet. There is strong evidence to support the expanding role of pharmacists as primary care providers in the corrections setting through activities such as direct patient care, health care clinics, and medication management.